THE POLITICIZATION OF SECURITY ISSUES IN POLITICAL LEADERSHIP: A STUDY ON THE “ASING DAN ASENG” NARRATIVE IN INDONESIAN ELECTIONS - Suharjimantoro, Suharjimantoro; Lutfie, Ratu Zahirah (JWP (Jurnal Wacana Politik), 2025)
This study investigates the politicization of security issues in Indonesian electoral politics through the construction and mobilization of the “Asing dan Aseng” narrative—a rhetorical strategy that depicts foreign influence and ethnic Chinese communities as existential threats to national sovereignty. The research aims to understand how political actors strategically use this narrative to mobilize voter support and legitimize their leadership. Using the theoretical lens of securitization and the politics of fear, the study applies a qualitative method based on critical discourse analysis of purposively selected campaign speeches, media coverage, and propaganda materials from the 2014 and 2019 presidential elections and the 2017 Jakarta gubernatorial election. The analysis reveals three dominant narrative frames: the portrayal of foreign economic control, ethnic scapegoating of Chinese Indonesians, and the betrayal of national interest by political elites. These narratives are conveyed through speech acts, media framing, and disinformation, transforming political competition into perceived national emergencies. The findings indicate that while effective in galvanizing electoral support, this strategy intensifies political polarization, delegitimizes opponents, and reinforces exclusionary populist nationalism. The study concludes that the instrumentalization of fear and identity in electoral politics poses serious threats to democratic integrity, social cohesion, and institutional legitimacy, calling for greater media literacy, counter-disinformation efforts, and democratic safeguards.